MEMAHAMI BERGERILYA LEWAT KOMUNIKASI PEMASARAN - Bayquni, Bayquni (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2010)
Marketing   communications    is a strategic  way to increase sales. However, not only until the Purchase  or intention to buy just  the marketing   communication  is possible,   even the values  contained  in a product  to the value required by the consumer  could  happen,  so consumers  no longer  buy products  diam buy a brand but also had to buy value. Thus when  designing   marketing communications   strategies  that build has perfect  accuracy  and carefulness both in its determination    of the marketing   mix  (Product,  Price, promotion  and place)  or in its selection   of promotion mix  (Personal   selling,  Direct Marketing,   PR  and Publicity,  Sales  Promotion,   Packaging,   and Word Of Mouth (WOM))  then  berhasil pula   marketing   communications   activities undertaken.   In this paper  we will study  how  to make  the precision   and accuracy   in using  marketing   communications,    better  known  by the name of integrated marketing   communications    (Integrated   Marekting  Communication).   Because   marketing   is very  heavy  with  the name  of competition   or in the  "war" then,  in this paper  were fitted  with use of the word guerrilla,   so what do the marketing   communication    really becomes  a strategy  appropriate.